Formulation and evaluation of interpenetrating polymeric network for controlled drug delivery. (3rd June 2021) - Batool, Nighat; Mahmood, Asif; Sarfraz, Rai Muhammad; Ijaz, Hira; Zafar, Nadiah; Hussain, Zahid
Abstract: Novel Cytarabine-loaded agarose and fenugreek-based hydrogel were formulated via the crosslinking process. Graft copolymerization of methacrylic acid (MAA) on agarose and fenugreek was carried out by using methylene bisacrylamide (MBA) as a crosslinker and potassium persulfate as an initiator. The influence of different formulation ingredients (fenugreek, agarose, MBA, MAA) on swelling index, percentage drug release, and percentage gel content were investigated. It was observed that an increase in the concentration of fenugreek and agarose resulted in an increase in the swelling index (72.45–97.17%). However, an increase in the amount of MBA led to a decrease in the swelling index from 74.23% to 57.74%. A similar result tendency was noted in the case of drug release. FTIR was employed to elucidate effective grafting. The thermal behavior of hydrogel was evaluated through TGA and DSC analysis whereas surface morphology was elucidated through SEM. Release studies were performed at both acidic and basic pH, that is, 1.2 and 7.4. Hence, formulated biocompatible hydrogels proved to be a promising system for the controlled delivery of Cytarabine.